THE CHARACTERISTIC FEATURES OF ARABIC RHETORIC IN ḤAYY IBN YAQẒAN BY IBN SINA AND ITS IMPACT ON THE DEVELOPMENT OF ARABIC STYLISTICS - Boburmirzo Mahkamboyev (Modern American Journals, 2026)
This article investigates Arabic rhetorical features in Ibn Sīnā’s Ḥayy ibn Yaqẓān, showing how symbolic narrative supports philosophical meaning. Using textual examples, it analyzes allegory (al-ramz), metaphor (istiʿāra)—especially light as knowledge—rhetorical economy (ījāz), and contextual appropriateness (murāʿāt muqtaḍā al-ḥāl). The study argues that these strategies enable clear, persuasive philosophical prose and influenced later Arabic stylistics by establishing restraint and clarity as key ideals.
Keywords: Arabic rhetoric, al-balāgha, Ibn Sīnā, Ḥayy ibn Yaqẓān, allegory, symbolism (al-ramz), metaphor (istiʿāra), rhetorical economy (ījāz), contextual appropriateness (muqtaḍā al-ḥāl), Arabic stylistics, philosophical prose